Association of Breastfeeding and Child Intelligence Quotient Score at Age 5 - Plunkett, Beth A. (Obstet Gynecol, 2021)
OBJECTIVE: To evaluate whether breastfeeding and its duration are associated with a reduced risk of low intelligence quotient (IQ) scores or other neurodevelopmental problems. METHODS: We conducted a secondary analysis of two parallel multicenter, double-blinded randomized controlled trials in which participants with a singleton pregnancy and either subclinical hypothyroidism or hypothyroxinemia were treated with thyroxine or placebo. Our primary outcome was low IQ score (<85 at age 5 by Wechsler Preschool and Primary Scale of Intelligence III). Secondary outcomes included performance measures on other validated neurodevelopmental tests. Univariable and multivariable analyses were performed to evaluate the association between breastfeeding and neurodevelopmental outcomes. Step-wise backward proceeding linear and logistic regression models were used to develop the final adjusted models. RESULTS: Of the 772 participants studied, 614 (80%) reported breastfeeding. Of these, 31% reported breastfeeding for <4 months, 19% for 4–6 months, 11% for 7–9 months, 15% for 10–12 months and 23% for >12 months. IQ scores were available for 756 children and mean age 5 scores were higher with any breastfeeding (96.7±15.1) than without (91.2±15.0, mean difference 5.5, 95% CI 2.8–8.2) and low IQ scores were less frequent with any breastfeeding (21.5%) than with no breastfeeding (36.2%, OR 0.48, 95% CI 0.33–0.71). In adjusted analyses, breastfeeding remained associated with reduced odds of low IQ (aOR 0.62, 95% CI 0.41–0.93) and each additional month of breastfeeding was associated with lower odds of a low IQ score (aOR 0.97, 95% CI 0.939–0.996). No significant associations between breastfeeding and other neurodevelopmental outcomes were identified in adjusted analyses. CONCLUSION: Breastfeeding and its duration are associated with lower odds of low IQ score at age 5.